2015
DOI: 10.4103/0019-5413.168765
|View full text |Cite
|
Sign up to set email alerts
|

Degenerated intervertebral disc prolapse and its association of collagen I alpha 1 Spl gene polymorphism

Abstract: Background:Degenerated disc disease (DDD) is a common disorder responsible for increased morbidity in a productive age group. Its etiology is multifactorial and genetic factors have been predominantly implicated. Disc prolapse results due to tear in the annulus, which is a fibrous structure composed largely of type I collagen. Functional polymorphism at the Sp1 site of the collagen I alpha 1 (COL1A1) gene has shown a positive association with DDD in Dutch and Greek populations. The purpose of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
(41 reference statements)
0
12
0
Order By: Relevance
“…No additional articles were selected through the manual search. Finally, seven studies [ 22 28 ] containing 1339 cases and 5406 controls fulfilled the predefined inclusion criteria and were included in the final analysis. The concrete characteristics of included studies were shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No additional articles were selected through the manual search. Finally, seven studies [ 22 28 ] containing 1339 cases and 5406 controls fulfilled the predefined inclusion criteria and were included in the final analysis. The concrete characteristics of included studies were shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Some of the articles included in the present study describe the level of diseases in their case group. We defined the severe degree of diseases as the patient who had a Kellgren score of 3 or greater in IVDD [ 28 , 32 ] and the patient who had a joint space narrowing(JSN) score ≥ 3 in OA [ 33 , 34 ] or took a joint replacement due to OA. We defined the mild or moderate degree of diseases as the patient who suffered OA or IVDD but did not satisfy the criterion mentioned above.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The COL1A1 gene is located on the long arm of chromosome 17 (17q21.3-q22) whereas the COL1A2 gene is located on the long arm of chromosome 7 (7q22.1). The COL1A1 gene consists of 52 exons and is 18kb in size 16 . It has been found that the substitution of G to T at the binding site of Sp1 (rs1800012) consequently led to enhanced expression of proteins concomitant with the increased binding affinity of Sp1.…”
Section: Discussionmentioning
confidence: 99%
“…Women with bad obstetric history, Genetic syndromes, H/O exposure to radiation and chemicals, H/O hypertension, diabetes mellitus or Malignancy were excluded. Chromosomal analysis was carried out to find the effects of synthetic progesterone (Norethisterone) on human chromosomes in lymphocyte culture in vitro by the method routinely used in Genetic Laboratory as described by Anjankar SD et al [7]. All the 60 samples so collected were divided into 3 parts and group were named as A, B, & C. Group A with no progesterone exposure; Group B with 48 hours progesterone exposure at concentration of (75micro gm of Norethisterone/ ml of medium) and Group C with 48hours progesterone exposure at concentration of (100micro gm of Norethisterone /ml of medium).…”
Section: Methodsmentioning
confidence: 99%